2008
DOI: 10.17221/644-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional compositions and yield of sweet fennel cultivars - Foeniculum vulgare Mill. ssp. vulgare var.azoricum (Mill.) Thell

Abstract: abstract:In two-year trials taking place at the Faculty of Horticulture in Lednice (Mendel University of Agriculture and Forestry in Brno), three cultivars of sweet fennel (Foeniculum vulgare Mill. ssp. vulgare var. azoricum [Mill.] Thell) -Precoce di Bologna, Rudy F1 and Zefa Fino have been evaluated. The trials were conducted in two terms in each of the trial years (summer and autumn term). In the harvest time, nutritional value was evaluated: content of vitamin C, minerals (K, Na, Ca, Mg), dietary fibre, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 1 publication
4
5
0
1
Order By: Relevance
“…When comparing the average values of some wild species with their cultivated relatives (Mataix et al 1998;Souci et al 2008) there are many wild species that reach double values than cultivated ones, such as thistle (S. marianum); or 4 times greater, as in the case of chicory (C. intybus). The values of vitamin C, as well as the ratio AA/DHAA, obtained for F. vulgare were in agreement with the values obtained for cultivated varieties of the same species (8.7-34 mg/100 g) by Koudela and Petříková (2008), who also found high variability in vitamin C contents. On the contrary, Souci et al (2008) reported higher values of vitamin C in F. vulgare (93 mg/100 g), Taraxacum officinale (68 mg/100 g) and Allium porrum (24 mg/100 g) than those found in this study.…”
Section: Resultssupporting
confidence: 90%
“…When comparing the average values of some wild species with their cultivated relatives (Mataix et al 1998;Souci et al 2008) there are many wild species that reach double values than cultivated ones, such as thistle (S. marianum); or 4 times greater, as in the case of chicory (C. intybus). The values of vitamin C, as well as the ratio AA/DHAA, obtained for F. vulgare were in agreement with the values obtained for cultivated varieties of the same species (8.7-34 mg/100 g) by Koudela and Petříková (2008), who also found high variability in vitamin C contents. On the contrary, Souci et al (2008) reported higher values of vitamin C in F. vulgare (93 mg/100 g), Taraxacum officinale (68 mg/100 g) and Allium porrum (24 mg/100 g) than those found in this study.…”
Section: Resultssupporting
confidence: 90%
“…Table (2) showed that fennel seeds contained iron (6.33mg/g), zinc (2.89 mg/100g), calcium (583.6 mg/100g), manganese (209.35 mg/100g), magnesium (83.87mg/100 g), sodium (15.91mg/100 g), potassium (849.45 mg/100g) , phosphorus (470 mg/100g). These results agreed with those reported by Badgujar et al, (2014)& Bukhari et al, (2014 The data obtained in the present study are more or less in accordance with those reported by Koudela and Petříková (2008). Fennel seeds may be considered as a good source of K, Ca and Mg.…”
Section: Mineral Contents Of Fennel Seedssupporting
confidence: 94%
“…In this study four commonly available plant products as fennel seeds, tulsi leaves, sesame seeds and coconut were compared with CPP-ACP containing chewing gum for their effect on dental plaque. [21]. The results of the present study revealed that fennel chewing led to an increase in plaque pH, calcium and phosphate concentration.…”
Section: Discussionsupporting
confidence: 55%